Cambios en resonancia magnética funcional en estudiantes de medicina con y sin restricción moderada de sueño (2016)
Objective To describe the effects of moderate sleep deprivation in brain regions involved in cognitive inhibition processes, motor function, and phonological fluency using functional Magnetic Resonance Imaging (fMRI). Materials and methods A sample of 12 under-graduate and post-graduate medical students, between 20 and 40 years, were subjected to a follow-up of the number of hours of regular sleep in order compare to a moderate sleep deprivation after a nightshift. The d2 attention test and fMRI studies were used in both groups in order to evaluate motor function, verbal fluency and cognitive inhibition, or Stroop paradigms. The moderate sleep deprivation was at least 63% with respect to the regular sleep pattern during the previous week. Results Significant differences in brain activity were found in fMRI to measure motor function (P < 0.05) comparing regular sleep cycle and moderate sleep deprivation. The brain activity with fMRI Stroop paradigms and phonological fluency showed no significant differences between the two conditions, likewise with the psychological attention test d2. Discussion The fMRI showed interference on motor representation activations in moderate sleep deprivation. No significant differences in fMRI were found in the processes of cognitive inhibition or Stroop paradigms, in phonological fluency, or in the psychological attention test d2. These could be attributed to inadequate sleep deprivation or efficient compensation mechanisms in the subjects of this study. Conclusion There is a difference showed in fMRI on motor representation activations in moderate sleep deprivation. © 2016 Sociedad Argentina de Radiología.